1989
DOI: 10.1007/bf01055015
|View full text |Cite
|
Sign up to set email alerts
|

Chlorinated hydrocarbon levels in human serum: Effects of fasting and feeding

Abstract: Twenty healthy adult humans had serum samples drawn on four occasions within a 24-hr period: after a 12 hr overnight fast, 4-5 hr after a high fat breakfast, at midafternoon, and the next morning after another 12 hr fast. Nonfasting samples had 22% to 29% higher mean concentrations (p less than 0.05) than did fasting samples for polychlorinated biphenyls (PCBs, 4.81 vs 3.74 ng/g serum wt), hexachlorobenzene (HCB, 0.163 vs 0.134 ng/g serum wt), and p,p'-dichlorodiphenyl-dichloroethylene (p,p'-DDE, 6.74 vs 5.37 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
481
2
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 791 publications
(491 citation statements)
references
References 16 publications
6
481
2
1
Order By: Relevance
“…Among the positive studies, one (28) reported a significant difference in DDE between breast cancer case patients and controls, as well as an almost 4-fold increase in risk comparing the highest quintile of DDE to the lowest; however, the values for serum organochlorine levels were not lipid adjusted. PCB and DDE residue levels in serum are influenced by the amount of lipid in the serum (46) and adjustment is necessary to standardize blood residue measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Among the positive studies, one (28) reported a significant difference in DDE between breast cancer case patients and controls, as well as an almost 4-fold increase in risk comparing the highest quintile of DDE to the lowest; however, the values for serum organochlorine levels were not lipid adjusted. PCB and DDE residue levels in serum are influenced by the amount of lipid in the serum (46) and adjustment is necessary to standardize blood residue measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In 2000-2001, the children underwent detailed clinical examinations at 7 years of age, and serum samples were obtained from most of them. The serum lipid content was determined from enzymatic measurements of cholesterol and triglycerides (32). On the basis of determinations of PCB in maternal serum already carried out (30,31), a subgroup of mother and child pairs was selected for the purposes of the present study.…”
Section: Methodsmentioning
confidence: 99%
“…LDLc was calculated using the formula (9) LDL c = Total cholesterol -(HDL c+ TG/5). Serum total lipid content was calculated as recommended by Phillips and colleagues (10). Total serum lipid (mg/dl) = 2.27 x serum cholesterol (mg/dl) + serum tdglyceddes (mg/ dl) + 0.623.…”
Section: Methodsmentioning
confidence: 99%